Encyclopedia of foods : a guide to healthy nutrition (Academic Press, 2002)
The Encyclopedia of Foods: A Guide to Healthy Nutrition is a definitive resource for what to eat for maximum health as detailed by medical and nutritional experts. This book makes the connection between health, disease, and the food we eat. The Encyclopedia describes more than 140 foods, providing information on their history, nutrient content, and medical uses. The Encyclopedia also describes the "fit kitchen", including the latest in food safety, equipment and utensils for preparing fit foods, and ways to modify favorite recipes to ensure health and taste. * Details healthy eating guidelines based on the RDA food pyramid * Provides scientific basis and knowledge for specific recommendations * Beautifully illustrated * Extensive list of reliable nutrition resources * Describes the fit kitchen from the latest in food safety to equipment and utensils for preparing fit foods to ways to modify favorite recipes to ensure health and taste.